2013
DOI: 10.1002/jsfa.6271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc compounds on Fusarium verticillioides growth, hyphae alterations, conidia, and fumonisin production

Abstract: Zn compounds have advantages compared to other antifungal compounds. In particular, they are non-toxic for the organism in appropriate amounts. They could be studied further as potential fungicides in agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Previous research (Baider & Cohen, 2003;Helfenstein et al, 2015;Shi et al, 2006) reported positive effects of manganese-containing fungicides and zinc-containing agents on fungal diseases. Savi et al (2013) showed that zinc compounds significantly inhibited Fusarium verticillioides growth from ≥25 nmol/L concentration, and all treatments inhibited conidia production. Manganese-containing fungicides such as mancozeb could inhibit the growth of P. nicotianae, and the highest inhibition rate was 62.7% (Panek & Tomsovsky, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research (Baider & Cohen, 2003;Helfenstein et al, 2015;Shi et al, 2006) reported positive effects of manganese-containing fungicides and zinc-containing agents on fungal diseases. Savi et al (2013) showed that zinc compounds significantly inhibited Fusarium verticillioides growth from ≥25 nmol/L concentration, and all treatments inhibited conidia production. Manganese-containing fungicides such as mancozeb could inhibit the growth of P. nicotianae, and the highest inhibition rate was 62.7% (Panek & Tomsovsky, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…In other research (Helfenstein et al, 2015;Li et al, 2016), zinc-containing agents could directly act on pathogens, initiate plant defenses, and reduce the virulence of pathogenic bacteria, thereby lessening bacterial plant damage. Savi et al (2013) demonstrated that Zn compounds efficiently reduced fungal growth and fumonisin production, with the best results obtained from zinc perchlorate. At present, the inhibition mechanisms of manganese and zinc on sporangiogenesis of P. nicotianae are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in staining was observed under light microscope at 400x and evaluated following Semighini and Harris () and Savi et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…Finally, the hyphae were washed with sterile distilled water to remove excess stain. The difference in staining was observed under light microscope at 400x and evaluated following Semighini and Harris (2010) and Savi et al (2013).…”
Section: Evans Blue Staining: Visualization Of Hyphal Alterationsmentioning
confidence: 99%
“…Finally, the hyphae were washed with sterile distilled water to remove excess stain. The difference in staining was observed under light microscope at 400× and evaluated, following References [52,53].…”
Section: Evans Blue Staining: Visualization Of Hyphal Alterationsmentioning
confidence: 99%